2002
DOI: 10.1111/j.1365-2621.2002.tb11386.x
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Isolate/Corn‐Zein Laminated Films: Transport and Mechanical Properties

Abstract: Soy protein films were thermally laminated with either single or double coats of corn-zein. Microstructural characterization of the surfaces and cross-sections reveals a ductile protein matrix of the soy component, but a brittle layered structure for the corn-zein component. The hydrophobic nature of the corn-zein improved the water vapor barrier properties of the laminates, while the superior oxygen barrier characteristics remained unaffected, as compared with the base soy film. The haze values of the laminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 17 publications
2
47
0
2
Order By: Relevance
“…Although the use of polylactic acid (PLA), thermoplastic starch and regenerated cellulose to coat paper has been tried in industrial applications, the penetration in the market is limited to now. Legislations on end of life packaging and consumer awareness drive the need to replace the use of depleting fossil resources by renewable ones and to reduce the environmental impacts of packaging [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of polylactic acid (PLA), thermoplastic starch and regenerated cellulose to coat paper has been tried in industrial applications, the penetration in the market is limited to now. Legislations on end of life packaging and consumer awareness drive the need to replace the use of depleting fossil resources by renewable ones and to reduce the environmental impacts of packaging [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Sabato et al (2001) found that cross linking with irradiation and thermal treatment improved the mechanical properties of soy protein and whey protein based films. Proteins treated by alkali, acid, solvents or heat are partially denatured and when these extended structures associate through hydrogen, ionic, hydrophobic and covalent bonding they form a film matrix (Pol et al 2002). Brandenburg et al (1993) reported the effect of pH on mechanical and barrier properties of soy protein films.…”
Section: Introductionmentioning
confidence: 99%
“…These represent the structures required for film formation. Protein films are formed when these structures associate through noncovalent and covalent bonding to form the protein matrix 6 . Low molecular weight plasticizers such as glycerol, sorbitol and potassium sorbate are added to proteins to improve the flexibility of the polymer by reducing the inter-chain interactions 1 .…”
Section: Introductionmentioning
confidence: 99%